Paclitaxel, Ifosfamide, and Cisplatin Efficacy for First-Line Treatment of Patients With Intermediate- or Poor-Risk Germ Cell Tumors - Feldman, Darren R. (J Clin Oncol, 2016)
PURPOSE: Paclitaxel, ifosfamide, and cisplatin (TIP) achieved complete responses (CRs) in two thirds of patients with advanced germ cell tumors (GCTs) who relapsed after first-line chemotherapy with cisplatin and etoposide with or without bleomycin. We tested the efficacy of first-line TIP in patients with intermediate- or poor-risk disease. PATIENTS AND METHODS: In this prospective, multicenter, single-arm phase II trial, previously untreated patients with International Germ Cell Cancer Collaborative Group poor-risk or modified intermediate-risk GCTs received four cycles of TIP (paclitaxel 240 mg/m(2) over 2 days, ifosfamide 6 g/m(2) over 5 days with mesna support, and cisplatin 100 mg/m(2) over 5 days) once every 3 weeks with granulocyte colony-stimulating factor support. The primary end point was the CR rate. RESULTS: Of the first 41 evaluable patients, 28 (68%) achieved a CR, meeting the primary efficacy end point. After additional accrual on an extension phase, total enrollment was 60 patients, including 40 (67%) with poor risk and 20 (33%) with intermediate risk. Thirty-eight (68%) of 56 evaluable patients achieved a CR and seven (13%) achieved partial responses with negative markers (PR-negative) for a favorable response rate of 80%. Five of seven achieving PR-negative status had seminoma and therefore did not undergo postchemotherapy resection of residual masses. Estimated 3-year progression-free survival and overall survival rates were 72% (poor risk, 63%; intermediate risk, 90%) and 91% (poor risk, 87%; intermediate risk, 100%), respectively. Grade 3 to 4 toxicities consisted primarily of reversible hematologic or electrolyte abnormalities, including neutropenic fever in 18%. CONCLUSION: TIP demonstrated efficacy as first-line therapy for intermediate- and poor-risk GCTs with an acceptable safety profile. Given higher rates of favorable response, progression-free survival, and overall survival compared with prior first-line studies, TIP warrants further study in this population.